2018
DOI: 10.1007/s00417-018-4157-8
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the sweet taste receptor T1R3 by sucralose attenuates VEGF-induced vasculogenesis in a cell model of the retinal microvascular endothelium

Abstract: BackgroundOne of the most prevalent microvascular complications for patients with diabetes is diabetic retinopathy (DR) associated with increased retinal endothelial blood vessel formation. Treatments to reduce vascularisation in the retinal endothelium are linked to improved sight in patients with DR. Recently, we have demonstrated the novel protective role of the artificial sweetener, sucralose, and the sweet taste receptor, T1R3, in the pulmonary endothelium to reduce vascular leak. In the present study, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 42 publications
(74 reference statements)
3
18
0
Order By: Relevance
“…Several studies indicate the possibly beneficial effect of some sweeteners for health [25, 26], but it is well known that fructose intake induces hypertension and impairs vascular contraction and relaxation [15, 27, 28]. In our study, high-fructose intake increased BP and body weight (Fig.…”
Section: Discussionsupporting
confidence: 51%
“…Several studies indicate the possibly beneficial effect of some sweeteners for health [25, 26], but it is well known that fructose intake induces hypertension and impairs vascular contraction and relaxation [15, 27, 28]. In our study, high-fructose intake increased BP and body weight (Fig.…”
Section: Discussionsupporting
confidence: 51%
“…It is therefore vital to understand the molecular mechanisms which underlie neovascularisation in DR pathology, and use this information to develop therapeutic options for patients. We have previously identified the presence of novel GPCRs, T1R2/3, in human retinal microvascular endothelial cells, which are activated by a range of acutely sweet molecules (Lizunkova et al 2019). Our studies demonstrated that the sweetener, sucralose, blocked VEGF-induced angiogenic processes such as permeability and neovascularisation, in the human retinal microvasculature.…”
mentioning
confidence: 65%
“…For the Nox4 activity kit (Cusabio, Texas, USA), the assay was performed as per the manufacturer's protocol and absorbance was measured at 450nm using a microplate reader (Tecan Sunrise). Angiogenic processes were measured as cell proliferation, migration, adhesion and neovascularisation as previously described (Lizunkova et al 2019). In brief, RMVEC were quiesced for 24 h with 1% FBS followed by exposure to bevacizumab, L, Z or combined treatment, in the presence and absence of VEGF, for 6 h. Alternatively, cells were exposed to bevacizumab, L, Z or combined treatment, with VEGF (50 ng/ml), in the presence of GLX7013114 (1 µM) (Raystar Bio, Hangzhou Guangyuan, China) or the vehicle control (DMSO).…”
mentioning
confidence: 99%
“…Cell viability of LMVEC transfected with miRNA mimics was assessed using CCK8 assay, as per the manufacturer’s guidelines, with absorbance read at 450 nm. 25…”
Section: Methodsmentioning
confidence: 99%
“…The pellet, comprising of EDEVs, was resuspended in sterile Dulbecco's PBS (DPBS) for permeability assays and quantification using qNano Gold (Izon Science) at 0.5 V, 45 mm stretch, 15 mbar pressure, using the NP200 pore and normalized to media as a control, RNAlater for miRNA analysis, or lysed for protein concentration analysis. 23,24 Permeability measurements Changes in monolayer resistance were measured using the electrical cell impedance sensor (ECIS) technique and fluorescein isothiocyanate (FITC) dextran permeability technique 25 as previously described. 17 Naı¨ve, un-transfected LMVECs were plated on collagen-coated ECIS arrays or Transwell inserts and cultured for 24 h, prior to exposure to freshly-prepared EDEVs, in the presence and absence of LPS (1 mg/ml).…”
Section: Extracellular Vesicle Isolationmentioning
confidence: 99%